2012
DOI: 10.1104/pp.111.188789
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of ArabidopsisMIR168aandARGONAUTE1Homeostasis in Abscisic Acid and Abiotic Stress Responses  

Abstract: The accumulation of a number of small RNAs in plants is affected by abscisic acid (ABA) and abiotic stresses, but the underlying mechanisms are poorly understood. The miR168-mediated feedback regulatory loop regulates ARGONAUTE1 (AGO1) homeostasis, which is crucial for gene expression modulation and plant development. Here, we reveal a transcriptional regulatory mechanism by which MIR168 controls AGO1 homeostasis during ABA treatment and abiotic stress responses in Arabidopsis (Arabidopsis thaliana). Plants ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 76 publications
(123 reference statements)
5
143
0
Order By: Relevance
“…These results support the idea of the involvement of AGO1 in the plant physiological response to salinity. A similar stress-related phenotype has already been described for another ago1 mutant, ago1-27 (Li et al, 2012b). However, no difference was observed between wild-type and ago1-11 plants when the expression of three salt-stress-related genes, ABF3, LEA4-5, and TSPO, was determined before and after NaCl treatment: in both wild-type and ago1-11 plants, overexpression of the stress marker genes was observed (Supplemental Fig.…”
Section: Ago1 Stabilizes Selected Mirna Molecules In Response To Saltmentioning
confidence: 70%
See 3 more Smart Citations
“…These results support the idea of the involvement of AGO1 in the plant physiological response to salinity. A similar stress-related phenotype has already been described for another ago1 mutant, ago1-27 (Li et al, 2012b). However, no difference was observed between wild-type and ago1-11 plants when the expression of three salt-stress-related genes, ABF3, LEA4-5, and TSPO, was determined before and after NaCl treatment: in both wild-type and ago1-11 plants, overexpression of the stress marker genes was observed (Supplemental Fig.…”
Section: Ago1 Stabilizes Selected Mirna Molecules In Response To Saltmentioning
confidence: 70%
“…Moreover, a more recent genome-wide analysis revealed that human AGO1 binds preferentially to active transcriptional enhancers and that this association is mediated by the RNAs that are transcribed from these enhancers, the eRNAs. Interestingly, the interaction of AGO1 with enhancers does not appear to regulate the transcription of neighboring genes but of alternative and constitutive splicing (Li et al, 2012b). Thus, in animal cells, the nuclear role of AGO1/2 proteins in the regulation of transcription and splicing has been well documented.…”
Section: Ago1 Acts Cotranscriptionally On Mir161 and Mir173 Genesmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, TFmiRNA regulation was studied by constructing a small subnetwork containing 24 TF-miRNA targets for 14 TFs and 10 target miRNAs (Supplemental Data Set 6). One of the retrieved interactions is the known binding of the ABRE BINDING FAC-TOR1 (ABF1) to the promoter of mir168a (Li et al, 2012). Another interesting, however unconfirmed, interaction is that between AP2 and mir167a, the latter which is known to play a role in flowering maturation (Rubio-Somoza and Weigel, 2013).…”
Section: Construction and Biological Evaluation Of An Arabidopsis Genmentioning
confidence: 99%